Disulfide‐Based Self‐Immolative Linkers and Functional Bioconjugates for Biological Applications - Deng, Zhengyu; Hu, Jinming; Liu, Shiyong (Macromolecular rapid communications., 2020)
It is of vital importance to reversibly mask and selectively activate bioactive agents for advanced therapeutic and diagnostic purposes, aiming to efficiently suppress background interferences and attenuate systemic toxicity. This strategy has been involved in diverse applications spanning from chemical/biological sensors and diagnostics to drug delivery nanocarriers. Among these, redox‐responsive disulfide linkages have been extensively utilized by taking advantage of extracellular and intracellular glutathione (GSH) gradients. However, direct conjugation of cleavable triggers to bioactive agents through disulfide bonds suffers from bulky steric hindrance and limited choice of trigger–drug combinations. Fortunately, the emergence of disulfide self‐immolative linkers (DSILs) provides a general and robust strategy to not only mask various bioactive agents through the formation of dynamic disulfide linkages but also make it possible to be selectively activated upon disulfide cleavage in the reductive cytoplasmic milieu. In this review, recent developments in DSILs are focused with special attention on emerging chemical design strategies and functional applications in the biomedical field. The universal redox gradients across cell membranes offer opportunities to design triggered release systems in response to intracellular reductive milieu. Recent developments of disulfide‐based self‐immolative linkers and their applications toward the construction of bioconjugates of drugs and imaging probes for therapeutic and diagnostic purposes are summarized.